Risk Assesment of Air Pollution Exposure (NO2, SO2, Total Suspended Particulate, and Particulate Matter 10 micron) and Smoking Habits on the Lung Function of Bus Drivers in Palembang City - Sunarsih, Elvi; Suheryanto, Suheryanto; Mutahar, Rini; Garmini, Rahmi (UI Scholars Hub, 2019)
Nitrogen dioxide (NO2), carbon monoxide (CO), sulfur dioxide (SO2), Particulate Matter (PM10) and TSP are the most common and harmful air pollutants to humans. In short period, air pollution exposure at 5 ppm for 10 minutes to humans causes dyspnea, and when the level is increase to 800 ppm could cause 100% mortality in animals. This study was an analytical research, with cross sectional design and risk analysis. One hundred subjects were analyzed in this study. The results showed that non-cancer Hazard Index (HI) for realtime exposure with mean value was NO2: 1.85; SO2: 2.92; TSP: 7.09; and PM10: 11.7 (HI value ≥1). The results of the analysis test for FVC lung capacity to non-cancer risk estimation of NO2, SO2, TSP and PM10 indicated that there was no significant relationship (p > 0,05). Variable of smoking habit is the most dominant variable (OR = 12,542) which affect respiratory disorders. The exposure of NO2, SO2, TSP and PM10 in Palembang City bus drivers is considered risky to non-cancer health subjects, so control is needed. This control could be performed by lowering the level of inhalation intake (I) of the RfC and the first simulation model for exposure could start from the second year to the sixth year.